Teaching concepts about the participation of girls, boys and adolescents - Ochoa Cervantes, Azucena (IE Revista de Investigación Educativa de la REDIECH, 2021)
The discourses and teaching practices are organised through participatory structures in which teaching and socialisation are developed. Various studies show that teaching concepts influence teaching practices. We consider it important to analyse the teaching concepts about student participation due to its impact on citizen training. A qualitative study was carried out to analyse the discourse of 30 teachers and 4 primary and secondary school principals in relation to practices promoting student participation. The results indicate that the concept of participation and its practices are rigid, limited to classroom activities, and oral language is the privileged medium for them to take place, which does not allow the creation of a conducive learning environment for students to develop the necessary skills to participate, thus limiting the exercise of their citizenship.